Voluntary early retirement: Between desires and necessities - Nathalie Burnay (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article aims at determining which are the most important personal and professional factors that can lead someone to bring to an end his/her professional career before the legal retirement age.We will first have to determine the profile of a worker who is tempted by an early retirement. What is the social mechanism that allows for a differentiation in this wish for retirement that is unequally distributed within the population?Secondly, we will analyse the main reasons brought forward by the workers to leave anactive professional life before due time: these might be health-linked, professional (too heavy physical work, psycho-social burdens, work schedules) and private reasons.This article is based on data collected from 812 workers, within 12 different activity sectors in Belgium in 2005.